The heterogeneous impact of taxation on economic development: New insights from a panel cointegration approach - Durusu-Ciftci, Dilek; Gokmenoglu, Korhan K.; Yetkiner, Hakan (Elsevier, 2018)
In this paper, we study the role of taxation on long-run income performance. In the theoretical part of the study, we develop a stylized model based on Barro (1990), in which income taxation has two contradictory roles in the standard Solow (1956) setup: on the one hand, taxation appropriates resources that would otherwise be used for physical capital accumulation, and on the other, it is the source of government spending, which is used to support private production. In the empirical part of the study, the impact of consumption tax, personal income tax, corporate profit tax and property tax on income is estimated using the common correlated effects (CCE) panel cointegration approach, which allows for cross-sectional dependencies and provides both panel and country-specific results. The panel findings for 30 OECD countries for the period of 1995-2016 indicate that only consumption tax has a statistically significant negative effect on long-run income. However, because the type and sign of the tax coefficients are heterogeneous for the country-specific results, we conclude that taxation has heterogeneous effects on income.
Keywords: Taxation; Economic development; Common correlated effects; Cross-sectional dependency